Prenatal and neonatal diagnosis of congenital lung lesions and their management - Peeka, Syam Babu; Srinivas, Srirampur; Reddy, Kota Ramesh (International Surgery Journal, 2019)
Background: The therapeutic strategy for congenital lung lesions remains controversial. The majority of the patients with congenital lung lesions do not present with complications. Some authors report that there should be no indication of surgical intervention for babies with no symptoms.Conversely, other authors recommend elective surgery, because the wait-and-see strategy might only increase the risk of abscess formation or the development of severe lung infections. The aims of the study was to evaluate cases with congenital lung lesions presented to pediatric Surgical department with an objective of assessing age and sex distribution, clinical features, diagnosis, management and outcomes. Methods: Prospective and retrospective study in Department of Pediatric Surgery, all cases of congenital lung lesions diagnosed antenatally and in neonatal period. Total 45 Patients were included. Results: Postoperative complications seen in 8 patients with morbidity about 25%. The surgical outcome is favorable, with manageable complications. Surgical intervention in asymptomatic patients is suggested. As the incidence of symptomatic, patients is highest between 1 to 6 months. Recommend elective surgery at 1 month of age. Surgery in asymptomatic patients is less invasive and in the infancy it is safer and more beneficial. Conclusions: Neonates, infants, and children presenting with respiratory distress due to these developmental anomalies may require urgent surgical intervention. Plain X-ray chest and CECT scan of the thorax are usually sufficient for diagnosis and planning of treatment. Lobectomy is the procedure of choice.